2020
DOI: 10.32942/osf.io/h97pw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential long-distance dispersal of freshwater diatoms adhering to waterfowl plumage

Abstract: Waterfowl are potential long-distance dispersal vectors for aquatic microbes such as diatoms, but experimental evidence is scarce. We conducted an experiment designed to emulate diatom dispersal via adherence to waterfowl, and to evaluate the effects of humidity and transport duration on potential dispersal success. We dipped individual mallard breast feathers in a pure benthic diatom culture (Nitzschia pusilla Grunow), then subjected them to one of four relative humidity levels (RH; from ca. 8% to 88%) cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…For example, direct terrestrial connections with lower latitudes must have allowed for stepwise short-distance dispersal, which is expected to be more effective for survival than long-distance dispersal over large maritime barriers. In that sense, migration of freshwater diatom species in the Arctic has likely been facilitated by both aeolian pathways and animal vectors ( 42 ). This includes the Arctic’s avian fauna, which is far richer than in Antarctica.…”
Section: Discussionmentioning
confidence: 99%
“…For example, direct terrestrial connections with lower latitudes must have allowed for stepwise short-distance dispersal, which is expected to be more effective for survival than long-distance dispersal over large maritime barriers. In that sense, migration of freshwater diatom species in the Arctic has likely been facilitated by both aeolian pathways and animal vectors ( 42 ). This includes the Arctic’s avian fauna, which is far richer than in Antarctica.…”
Section: Discussionmentioning
confidence: 99%
“…Both epizoochory and endozoochory are important for microbial dispersal by waterbirds, but it is unclear which mechanism is dominant. Manning et al (2021) investigated the potential of epizoochory by dipping breast feathers from mallards Anas platyrhynchos in cultures of diatoms and showed that their survival when stuck to feathers increases with relative air humidity. Tesson et al (2018) used in vitro gut‐simulation to investigate the endozoochory potential of dinoflagellates, confirming that resting cysts survived gut conditions.…”
Section: Understudied Role Of Waterbirds As Vectors For Microbesmentioning
confidence: 99%
“…Sensitivity analysis for wintering waterbirds suggests that maximum gut retention times have less influence on seed dispersal kernels than the nature of bird movements per se, reinforcing the need to include quality tracking data to obtain valid predictions (Martín‐Vélez, Leeuwen, et al, 2021). Some studies of endozoochory have made unrealistic estimates of the scale of dispersal, as they fail to accurately account for waterbird movement, and make simple extrapolations from a retention time curve by assuming propagule ingestion is followed by non‐stop flights (e.g., Manning et al, 2021; Raulings et al, 2011). However, ringing recoveries have been used to make general predictions for kernels during seasonal migration, and have shown that migrating ducks can facilitate dispersal on a very large scale, predicting dispersal of over 3.5% of seeds to be over 100 km and up to 1,600 km, although maximum dispersal distances for Artemia cysts were about half that of seeds (Viana et al, 2013).…”
Section: Understanding Waterbird Movements and Modelling Zoochorymentioning
confidence: 99%